Proceso de atención de enfermería en gestante de 15 semanas de gestación con diagnóstico de colestasis intrahepática gestacional. - Monserrate Murillo, Andy Caleb (2024)
The present investigation is related to a 30-year-old patient diagnosed with gestational intrahepatic cholestasis, whose objective was to apply the nursing care process to the patient. Therefore, integral observation of the case, data collection and bibliographic review of the patient's pathology were performed. The results are as follows: The development of nursing processes plays an essential and important role in healthcare practice because it helps us to obtain a more structured picture of the patient's needs from a critical assessment based on NANDA, NIC, NOC classification and satisfying each of them. The conclusions obtained from the present work are: prioritizing nursing diagnoses and developing a continuous care plan allows us to improve the patient's health and lifestyle.